2012
DOI: 10.3762/bjoc.8.234
|View full text |Cite
|
Sign up to set email alerts
|

The multicomponent approach to N-methyl peptides: total synthesis of antibacterial (–)-viridic acid and analogues

Abstract: SummaryTwo syntheses of natural viridic acid, an unusual triply N-methylated peptide with two anthranilate units, are presented. The first one is based on peptide-coupling strategies and affords the optically active natural product in 20% overall yield over six steps. A more economical approach with only four steps leads to the similarly active racemate by utilizing a Ugi four-component reaction (Ugi-4CR) as the key transformation. A small library of viridic acid analogues is readily available to provide first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This family of oligomers comprising poly- N -substituted glycines mimics the primary natural structure of peptides and exhibits greater proteolytic stability and increased cellular permeabilities in comparison to peptides [ 5 – 7 ]. A powerful synthetic tool for the preparation of a peptoid backbone is the Ugi four-component reaction (U-4CR) [ 8 14 ]. It has been demonstrated that the combination of multicomponent reactions with the use of microwave irradiation is able to efficiently produce complex molecules with a reduced number of steps and short reaction times [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This family of oligomers comprising poly- N -substituted glycines mimics the primary natural structure of peptides and exhibits greater proteolytic stability and increased cellular permeabilities in comparison to peptides [ 5 – 7 ]. A powerful synthetic tool for the preparation of a peptoid backbone is the Ugi four-component reaction (U-4CR) [ 8 14 ]. It has been demonstrated that the combination of multicomponent reactions with the use of microwave irradiation is able to efficiently produce complex molecules with a reduced number of steps and short reaction times [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…251−253 From a synthetic point of view, although this amino acid is notoriously difficult to acylate due to the lower nucleophilicity of the aromatic amino group. 251,254 The presence of a rare N-methyl-3-phenylserine residue is another interesting feature of asperterrestide A. A D-Ile residue is also present in its sequence.…”
Section: -Membered Ctpsmentioning
confidence: 99%
“…Asperterrestide contains the β-amino acid 2-amino benzoic acid (2-Abz or anthranilic acid), rendering a rigid, planar structure to the molecule . Anthranilic acid containing peptides are attractive as drug-like molecules, particularly because of this conformational restriction imposed by this amino acid residue. From a synthetic point of view, although this amino acid is notoriously difficult to acylate due to the lower nucleophilicity of the aromatic amino group. , The presence of a rare N -methyl-3-phenylserine residue is another interesting feature of asperterrestide A. A d -Ile residue is also present in its sequence.…”
Section: -Membered Ctpsmentioning
confidence: 99%
“…4 Hz),117.4,116.0 (d,3 J CF = 21.6 Hz); 19 F NMR (376 MHz, DMSO-d 6 ): δ −56.63, −112.65; IR (film) 2903,2676,1711,1622,1599,1473,1417,1246,1216,1175,1134,1037,881,881,810,776,650,553 2,benzoic Acid (17). 34 A flame-dried flask containing trifluoroacetic anhydride (0.56 mL, 4 mmol) was cooled to 0 °C. 2-Fluoro-4-aminobenzoic acid (0.155 g, 1 mmol) was added in portions, after which the flask was allowed to warm to rt while stirring for 2 h. The mixture was partitioned between 20 mL of ice water and 10 mL of CH 2 Cl 2 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%